2006
DOI: 10.1080/15533170500524496
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Carbon Nanotubes as Low Temperature Sensors

Abstract: Low-temperature resistance measurement of CVD-grown carbon nanotubes has been carried out. Carbon nanotubes (CNTs) were grown on nickel film deposited on float glass substrate using an ion beam deposition technique. It was observed that nickel metal on the float glass behaves as metal. CNT's grown on this film behave as semiconductors. The resistance variation in the temperature range is drastic and indicates that it can be used as a low-temperature sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Because of their good electrical response to the temperature variations, CNTs became a serious candidate as an emerging material to provide solutions for the future temperature sensors development. Both single and multiwall CNTs, having either metallic and semiconductor behavior, have been reported as temperature sensors [11,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55].…”
Section: Constructive Solutions For Temperature Sensors Based On Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their good electrical response to the temperature variations, CNTs became a serious candidate as an emerging material to provide solutions for the future temperature sensors development. Both single and multiwall CNTs, having either metallic and semiconductor behavior, have been reported as temperature sensors [11,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55].…”
Section: Constructive Solutions For Temperature Sensors Based On Cntsmentioning
confidence: 99%
“…There are a few structure designs, fabricated in batch assembly processes [59], but most of CNT-based sensors are produced in a serial assembly process, resulting in a low number of products. Over time, several assembling methods have been developed, including: direct growth on the substrate by chemical vapor deposition (CVD) process [29,30,31,32,33,34,53,54,55];thin films obtained by gluing [37,38], printing [35,36], filtration over a membrane [51,52], spraying [49,50,60];drop-casting deposition from a solution followed by a dielectrophoresis (DEP) procedure [39,40,41,46,47,61,62]. …”
Section: Constructive Solutions For Temperature Sensors Based On Cntsmentioning
confidence: 99%
“…Multiplexed arrays of nanowire sensors can be functionalized with different sensing affinities using microspotting methods used in biomolecular arrays, or by Dip Pen Nanolithography for other higher density systems. Nanosensors have already been made for rapid detection of metal ions [453], gases [454], biomolecules [455], temperature [456,457] and mechanical strain [458].…”
Section: Patterned Sams In Nanosciencementioning
confidence: 99%
“…Carbon nanotubes (CNTs) have been shown to have various potential applications [1][2][3][4][5][6] and have attracted signicant interest due to their very attractive mechanical and electrical properties. Recent studies have shown that carbon nanotubes (CNTs) can be used as temperature sensors [7][8][9][10][11][12] because the extremely small size of the CNT can provide accurate measurements at nanoscale size and reduce the possibility of disturbing the neighboring environment, which is very important in a complicated thermal ow system. The reported CNT-based temperature sensors can be categorized into thermal expansion and thermal resistance according to their different working principles.…”
Section: Introductionmentioning
confidence: 99%